Connecting Territories Exploring People and Nature, 1700-1850 - Boscani Leoni, Simona; Baumgartner, Sarah; Knittel, Meike (Emergence of Natural History, 2021)
The book analyses from a comparative perspective the exploration of territories, the histories of their inhabitants and local natural environments, covering different regions in Europe, the Americas and Asia, during the long eighteenth century. ; Readership: Institutes, scholars, students, academic libraries interested in Early Modern and Modern History, Postcolonial Studies, Latin American Studies, European Studies, History of Science, History of Medicine; Knowledge History; Social History; Rural History; Environmental Studies.